2000
DOI: 10.1046/j.1365-2036.2000.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of short versus long therapy with a proton pump inhibitor, clarithromycin and either metronidazole or amoxycillin for treating Helicobacter pylori infection

Abstract: Fourteen-day, proton pump inhibitor-based triple therapy achieves better results than 7-day schedules. Additional data are necessary to evaluate 10-day therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
128
2
9

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(152 citation statements)
references
References 29 publications
10
128
2
9
Order By: Relevance
“…Most of the recommendations by the consensus groups recommend a period of 7 days, especially because of the cost factor. In reality, meta-analysis studies have shown a 4% gain by extending to 10 days and 5% with 14 days (15,60,64,91) . For patients with a possible or proven history of penicillin allergy to the scheme described above is recommended replacing amoxicillin with the furazolidone 200 mg twice a day (31,35) .…”
Section: Statement 27mentioning
confidence: 99%
“…Most of the recommendations by the consensus groups recommend a period of 7 days, especially because of the cost factor. In reality, meta-analysis studies have shown a 4% gain by extending to 10 days and 5% with 14 days (15,60,64,91) . For patients with a possible or proven history of penicillin allergy to the scheme described above is recommended replacing amoxicillin with the furazolidone 200 mg twice a day (31,35) .…”
Section: Statement 27mentioning
confidence: 99%
“…The first method suggested that increasing the STT duration would improve treatment efficacy. In an early meta-analysis, a 14-d STT regimen raised the eradication rate compared to a 7-d regimen [71] . Another meta-analysis supported this result by showing that extending STT over 7 d improved the eradication rate [72] .…”
Section: Publication Treatment Duration Patients Therapy Regimen Eradmentioning
confidence: 99%
“…Antacids (aluminium hydroxide and magnesium trisilicate combination) are also used to decrease the gastric acid secretion (Rang et al, 2003). The drugs used for the treatment of H. pylori associated gastric and duodenal ulcers-triple therapy regimen, which includes a proton pump inhibitor (omeprazole, lansoprazole), antibiotics (clarithromycin and metronidazole) (Rakesh et al, 2010: Calvet et al, 2000: Enaganti, 2006.…”
Section: Treatment Strategiesmentioning
confidence: 99%